2004
DOI: 10.1159/000080201
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of Temporary Loop Ileostomies

Abstract: Background/Aims: A temporary loop ileostomy is constructed to protect a distal colonic anastomosis. Closure is usually performed not earlier than 8–12 weeks after the primary operation. During this period, stoma-related complications can occur and enhance the adverse effect on quality of life. The aim of this study was to evaluate the length of time between ileostomy construction and closure, to quantify stoma-related morbidity and to examine the potential advantages of early ileostomy closure. Methods: Sixty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
3
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 42 publications
4
98
3
4
Order By: Relevance
“…Some surgeons use a protective stoma after LAR to prevent anastomotic leakage in the hope that by diverting the fecal stream and keeping the anastomosis free of material, leakage will be less likely. While other surgeons have reported that covering the protective stoma had no influence on anastomotic leakage and reoperation rates, the further complications that can be caused by the stoma itself should not be ignored, as they include discomfort and inconvenience, high output with consequent dehydration, and anastomotic complications at the stoma closure site [12][13][14][15][16][17][18] . Although protective stomas are widely used in LAR for rectal cancer, it remains unclear whether such protective stomas are useful for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some surgeons use a protective stoma after LAR to prevent anastomotic leakage in the hope that by diverting the fecal stream and keeping the anastomosis free of material, leakage will be less likely. While other surgeons have reported that covering the protective stoma had no influence on anastomotic leakage and reoperation rates, the further complications that can be caused by the stoma itself should not be ignored, as they include discomfort and inconvenience, high output with consequent dehydration, and anastomotic complications at the stoma closure site [12][13][14][15][16][17][18] . Although protective stomas are widely used in LAR for rectal cancer, it remains unclear whether such protective stomas are useful for patients.…”
Section: Introductionmentioning
confidence: 99%
“…These complications were diagnosed according to standard predefined criteria and were based on those occurring most frequently2, 4, 16, 17, 18, 19, 20, 21, 22. General postoperative complications were recorded, including surgical‐site infection, abdominal abscess, ileus, abdominal fascia dehiscence, anastomotic leakage, pneumonia, urinary tract infection and a miscellaneous (other) group.…”
Section: Methodsmentioning
confidence: 99%
“…The morbidity rate is high, ranging from 21 to 60 per cent2. This results in decreased quality of life (QoL), and disturbed physical and psychological well‐being3, 4, 5, 6, 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent literature shows the overall stoma-related morbidity in such patients, may vary between 17 and 45 %. [1][2] It also reflects adversely with body image and quality of life. 3 The intension of the stoma creation is primarily a temporary one.…”
Section: Introductionmentioning
confidence: 99%